Pengaruh Pemberian Amelioran Organik dan Anorganik pada Media Subsoil Ultisol terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis jacq.) Di Pre Nursery - Alfian, Alfian; Nelvia, Nelvia; Amri, Al Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of the research was studied the effect of application of organik and inorganik ameliorants on the growth of pre nursery oil palm seed (Elaeis guineensis Jacq.) on Ultisol subsoil. This research was done at Bina Widya Campus of Riau University, Km. 12,5 Panam, Pekanbaru. The field research used Soil Science Laboratory and Agriculture Faculty. This research used statistic factorial in Completely Randomized Design (CRD). The first is organic ameliorant consist of oil palm empty fruit bunches compost (OPEFBC) and cocopeat (C) with 6 levels (O0= without ameliorant, O1= 100 g OPEFBC, O2= 100 g C, O3= 50 g OPEFBC + 50 g C, O4= 50 g OPEFBC + 100 g C, O5= 100 g OPEFBC + 50 g C), the second is inorganic ameliorant consist of drges and fly ash with 4 levels (A0= without  ameliorant, A1= 50 g dregs, A2= 50 g fly ash and A3= 25 g dregs + 25 g fly ash)/ 2 kg soils. The result of combination organic ameliorant (50 g OPEFBC + 100 g C) and inorganic ameliorant (50 g fly ash) increased plant hight, number of leaves, stem diameter and leaf area compared to control and application of organic ameliorant (100 g OPEFBC) and inorganic ameliorant (50 g dregs, fly ash or mix).  Keywords: OPEFBC, cocopeat, fly ash, dregs